2002
DOI: 10.1016/s0168-1923(02)00109-0
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance closure at FLUXNET sites

Abstract: A comprehensive evaluation of energy balance closure is performed across 22 sites and 50 site-years in FLUXNET, a network of eddy covariance sites measuring long-term carbon and energy fluxes in contrasting ecosystems and climates. Energy balance closure was evaluated by statistical regression of turbulent energy fluxes (sensible and latent heat (LE)) against available energy (net radiation, less the energy stored) and by solving for the energy balance ratio, the ratio of turbulent energy fluxes to available e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

218
1,470
4
34

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 2,051 publications
(1,726 citation statements)
references
References 69 publications
218
1,470
4
34
Order By: Relevance
“…The EBR results for the Skukuza eddy covariance system, which vary between 0.76 and 1.09 with an annual mean of 0.93 (only the years with high-quality data), are generally within the reported accuracies as shown in most studies that report the energy balance closure error at 10-30 %, across different ecosystems. For instance, Wilson et al (2002) also recorded an annual mean EBR of 0.84, ranging between 0.34 and 1.69 in an extensive study investigating 22 FLUXNET sites across the globe; EBR in ChinaFLUX sites ranged between 0.58 and 1.00, with a mean of 0.83 (Yuling et al, 2005); according to Were et al (2007), EBR values of about 0.90 were found over shrub and herbaceous patches in a dry valley in southeast Spain, whereas Chen et al (2009) showed a mean of 0.98 EBR for their study in the semi-arid region of Mongolia, and an EBR value of 0.80 was found by Xin and Liu (2010) in a maize crop in semi-arid conditions, in China. Using data from the Tibetan Observation and Research Platform (TORP), Liu et al (2011) observed an EBR value of 0.85 in an alfalfa field in semi-arid China.…”
Section: Surface Energy Balance Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The EBR results for the Skukuza eddy covariance system, which vary between 0.76 and 1.09 with an annual mean of 0.93 (only the years with high-quality data), are generally within the reported accuracies as shown in most studies that report the energy balance closure error at 10-30 %, across different ecosystems. For instance, Wilson et al (2002) also recorded an annual mean EBR of 0.84, ranging between 0.34 and 1.69 in an extensive study investigating 22 FLUXNET sites across the globe; EBR in ChinaFLUX sites ranged between 0.58 and 1.00, with a mean of 0.83 (Yuling et al, 2005); according to Were et al (2007), EBR values of about 0.90 were found over shrub and herbaceous patches in a dry valley in southeast Spain, whereas Chen et al (2009) showed a mean of 0.98 EBR for their study in the semi-arid region of Mongolia, and an EBR value of 0.80 was found by Xin and Liu (2010) in a maize crop in semi-arid conditions, in China. Using data from the Tibetan Observation and Research Platform (TORP), Liu et al (2011) observed an EBR value of 0.85 in an alfalfa field in semi-arid China.…”
Section: Surface Energy Balance Assessmentmentioning
confidence: 99%
“…For instance, Wilson et al (2002) comprehensively investigated the energy closure of the summer and winter seasons for 22 FLUXNET sites for 50 site-years. They also reported higher energy balance correlation during the wet compared to the dry season, with the mean R 2 of 0.89 and 0.68, respectively.…”
Section: Seasonal Variation Of Ebrmentioning
confidence: 99%
See 3 more Smart Citations